2016
DOI: 10.1111/inm.12245
|View full text |Cite
|
Sign up to set email alerts
|

Risky business: Lived experience mental health practice, nurses as potential allies

Abstract: Mental health policy includes a clear expectation that consumers will participate in all aspects of the design and delivery of mental health services. This edict has led to employment roles for people with lived experience of significant mental health challenges and service use. Despite the proliferation of these roles, research into factors impacting their success or otherwise is limited. This paper presents findings from a grounded theory study investigating the experiences of Lived Experience Practitioners … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 37 publications
0
33
0
Order By: Relevance
“…In particular, because of the interpersonal nature of their work, several researchers refer to the crucial position of mental health nurses to promote and take leadership in the implementation of peer worker roles (Byrne et al . ; Cleary et al . ; Hurley et al .…”
Section: Relevance For Practicementioning
confidence: 99%
See 1 more Smart Citation
“…In particular, because of the interpersonal nature of their work, several researchers refer to the crucial position of mental health nurses to promote and take leadership in the implementation of peer worker roles (Byrne et al . ; Cleary et al . ; Hurley et al .…”
Section: Relevance For Practicementioning
confidence: 99%
“…Several researchers point to the crucial position of mental health nurses to facilitate this authentic integration (Byrne et al . ; Hurley et al . ).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, one teaching staff member suggested that if a cotaught subject was to become a permanent part of the curriculum, “it would need review every semester, to make sure that the parties that were teaching were still good with it.” It is not usual practice to review curricula in this way. Negative attitudes of health professionals to working collaboratively with consumers are well referenced in the literature and presents a significant challenge, and there is no reason to assume nurse educators may not hold similar views. Truly collaborative approaches can be fostered and galvanized if accreditation guidelines more clearly require more consumer involvement in teaching, at least as a starting point.…”
Section: Discussionmentioning
confidence: 99%
“…Vigilance should be exercised regarding the peer workers' potential dependence on (mainly supervisory) care providers, which might risk diluting the specific added value of peer support. In this way, cooperation with peer workers can be enhanced, and a base can be created for jointly discussing and shaping role-related competences (Byrne et al 2016;Hurley et al 2016). In this perspective, supervision and support from people with lived experience should be promoted (Vandewalle et al 2016).…”
Section: Relevance For Practicementioning
confidence: 99%
“…They concluded that, compared to other caregivers, nurses were more resistant to the active participation of peer workers in the department. Yet while studies highlight defensive attitudes of nurses towards the integration of peer workers, several authors indicate that mental health nurses can play a key role in facilitating the integration of peer workers in mental health-care organizations (Byrne et al 2016;Cleary et al 2011;Compton et al 2014;Hurley et al 2016;Vandewalle et al 2016). Yet while studies highlight defensive attitudes of nurses towards the integration of peer workers, several authors indicate that mental health nurses can play a key role in facilitating the integration of peer workers in mental health-care organizations (Byrne et al 2016;Cleary et al 2011;Compton et al 2014;Hurley et al 2016;Vandewalle et al 2016).…”
Section: Introductionmentioning
confidence: 99%